Local knowledge and adaptation to climate change in natural resource-based societies of the Asia-Pacific - Louis Lebel (2018)
This paper reviewed 42 studies of how local knowledge contributes to adaptation to climate and climate change in the Asia-Pacific Region. Most studies focused on traditional ecological or indigenous knowledge. Three simple questions were addressed: (1) How are changes in climate recognized? (2) What is known about how to adapt to changes in climate? (3) How do people learn about how to adapt? Awareness of change is an important element of local knowledge. Changes in climate are recognized at multiple time scales from observations that warn of imminent extreme weather through expectations for the next season to identification of multi-year historical trends. Observations are made of climate, its impact on physical resources, and bio-indicators. Local knowledge about how to adapt can be divided into four major classes: land and water management, physical infrastructure, livelihood strategies, and social institutions. Adaptation actions vary with time scale of interest from dealing with risks of disaster from extreme weather events, through slow onset changes such as seasonal droughts, to dealing with long-term multi-year shifts in climate. Local knowledge systems differ in the capacities and ways in which they support learning. Many are dynamic and draw on information from other places, whereas others are more conservative and tightly institutionalized. Past experience of events and ways of learning may be insufficient for dealing with a novel climate. Once the strengths and limitations of local knowledge (like those of science) are grasped the opportunities for meaningful hybridization of scientific and local knowledge for adaptation expand. © 2012 Springer Science+Business Media B.V.